E-Advertorial Design using the Addie Model as a Marketing and Health Promotion Strategy - Susindra, Yoswenita; Ayu, Dessya Putri; Widyawati, Agatha; Kartika, Ria Chandra (International Journal of Healthcare and Information Technology, 2024)
Teaching factory Nutrition Care Center (NCC) is a nutrition service center for the wider community in health consultations, but so far patients only come from internal campuses. NCC has experienced a decline in the number of visits every months. The decrease in the number of visits to NCC may be caused by many things, and one of them caused by the marketing strategy. NCC needs to introduce its products by using effective messages such as e-advertorials. E-advertorials are more effective in creating brand awareness than other advertisements. The aim of this research is to design an EAdvertorial as a marketing and health promotion strategy to introduce NCC service products to the general public and increase patient visits. The research method uses a qualitative approach with descriptive qualitative research type. The design study was research and development. Data collected by questionnaire, interview, and literature study. The development of E-Advertorial uses ADDIE model. The results of the validation assessment score is 90.8%, which means this media is suitable for publication. The feasibility test assessment score is 80%, which means the E-Advertorial media is very good. E-advertorials can be used as a eligible promotional medium that is interesting, informative and easily accessible.